Maxillary and Frontal Bone Simultaneously Involved in Brown Tumor due to Secondary Hyperparathyroidism in a Hemodialysis Patient - Suheil Artul; Abdalla Bowirrat; Mustafa Yassin; Zaher Armaly (Case Reports in Oncological Medicine)
Brown tumors are rare focal giant cell lesions of the bone caused by primary hyperparathyroidism (HPT). Brown tumor was reported in 1891; it presents as the end-stage findings of HPT. Common involvements are skull and pelvic girdle. We describe a case of 46-year-old female hemodialysis patient, with secondary HPT in whom multiple masses lesions of the left maxillary sinus and frontal bone were radiologically suspected to be brown tumor. This unusual manifestation of secondary HPT can be expected to occur with increased longevity of patients with renal failure and illustrates the need to include brown tumor in the differential diagnosis.